Mentoring and Succession of Administrators: Critical Issues in Public and Private Secondary Schools in Lagos State, Nigeria - S.A. Oladipo; A.B. Adebakin; O.F. Iranloye (University of Sofia, 2016)
Studies have shown that the quality of outcome in Nigerian secondary schools is declining at an alarming rate due to shortage of required resources as well as leadership challenges. The challenges have been observed to be as a result of lack of mentoring which is not a common practice in school management in Nigeria. Consequently, this study investigated the extent to which mentoring as a strategy for administrators' succession plan impacts on the performance of their duties in public and private secondary schools in Lagos, Nigeria. The study adopted the descriptive survey design and administered a 25-item self-constructed questionnaire on participants. A total of 530 participants were randomly selected from the population of 4,350 senior teachers. The Participants were drawn from 145 secondary schools (91 public and 54 registered private) in Education District IV of Lagos State. The findings showed that mentoring has significant impact on administrators' succession planning and that succession planning does not significantly differ in public and private secondary schools in Lagos State. The study concluded that leadership development is a critical factor in secondary school effectiveness and efficiency. Therefore, serving administrators as well as prospective administrators should be regularly evaluated to determine their training needs at different career stages. There should also be mentoring related policies to enhance the managerial skills, sense of competence and effectiveness of the prospective administrators.